MODEL PENILAI SAHAM: SEBUAH SYSTEMATIC LITERATURE REVIEW - Irsyad Haryono Aulia; Endang Ruhiyat; Nofryanti Nofryanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to review and synthesize empirical findings on the use of asset pricing models in portfolio analysis, including the Capital Asset Pricing Model (CAPM), Fama–French models (three- and five-factor), the Carhart four-factor model, and the Arbitrage Pricing Theory (APT), over the period 2014–2025. The research employs a Systematic Literature Review (SLR) with a qualitative approach, conducted through systematic identification, selection, quality assessment, and synthesis of relevant national and international scholarly articles. The results indicate that no single asset pricing model demonstrates universal superiority across all market conditions. CAPM remains widely applied due to its simplicity and ease of implementation, although its explanatory power is often limited in dynamic markets. Multifactor models such as Fama–French and Carhart generally provide stronger explanatory power, particularly in developed markets, but yield inconsistent results in emerging markets, including Indonesia. Meanwhile, APT offers greater flexibility in factor selection but faces challenges in identifying empirically stable and relevant risk factors. This study concludes that differences in market characteristics, investor behavior, macroeconomic conditions, and research methodologies are the main sources of empirical inconsistency across asset pricing models. These findings imply that the selection of asset pricing models should be context-dependent and aligned with analytical objectives, highlighting the importance of comparative and contextual approaches in portfolio analysis within the Indonesian capital market.